PENGARUH PENDEKATAN PROBLEM BASED LEARNING BERBANTUAN MASALAH OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR KRITIS DITINJAU DARI SIKAP MATEMATIS SISWA [THE INFLUENCE OF THE PROBLEM-BASED LEARNING MODEL ASSISTED BY OPEN-ENDED PROBLEMS TOWARDS MATHEMATICAL CRITICAL THINKING SKILLS BASED ON STUDENTS' MATHEMATICAL ATTITUDE] - Gunur, Bedilius; Ramda, Apolonia Hendrice; Makur, Alberta Parinters (JOHME: Journal of Holistic Mathematics Education, 2019)
This research aimed to: 1) compare the mathematical critical thinking skills of students who were taught with the Problem Based Learning model assisted by open-ended problems and students who were traditionally taught, 2) investigate the interaction between problem based learning models with mathematical attitudes towards students' mathematical critical thinking abilities. It was a quantitative study using a quasi-experimental method with a 2 x 2 factorial design and was conducted at SMA Negeri 1 Cibal, Manggarai district, East Nusa Tenggara. Two classes were experimental and two classes were control and were chosen using cluster random sampling techniques. Data were obtained through questions to measure mathematical critical thinking skills and mathematical attitude questions and then analyzed with two way ANOVA. The data analysis and interpretation showed that 1) the mathematical critical thinking skills of students who were taught with the Problem Based Learning model assisted by open-ended problems were better than those of students who have been traditionally taught 2) there was no interaction between the problem based learning model and students' mathematical critical thinking abilities. This means that both students who had high and low mathematical attitudes scores when taught with the Problem Based Learning approach assisted with open-ended problems were always better than students who are taught with conventional approaches.BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk; 1) membandingkan kemampuan berpikir kritis matematika siswa yang mengikuti model problem based learning berbantuan masalah open-ended dengan kemampuan berpikir kritis matematika siswa yang mengikuti pembelajaran konvensional. 2) melihat interaksi antara model problem based learning dengan sikap matematis terhadap kemampuan berpikir kritis matematika siswa. Penelitian ini merupakan penelitian eksperimen semu (quasi experiment) dengan rancangan factorial 2 x 2. Populasi dalam penelitian ini adalah siswa kelas X SMA Negeri 1 Cibal kabupaten Manggarai, Nusa Tenggara Timur. Pengambilan sampel dilakukan dengan menggunakan teknik cluster random sampling, 2 kelas sebagai kelas eksperimen dan 2 kelas sebagai kelas kontrol. Instrumen penelitian yang digunakan berupa tes kemampuan berpikir kritis matematika dan tes sikap matematis. Data yang telah terkumpul dianalisis dengan menggunakan uji Anava Dua Jalur. Sebelum digunakan uji anava dua jalur, data tersebut terlebih dahulu dilakukan uji normalitas dan homogenitas. Hasil penelitian ini menunjukkan; 1) kemampuan berpikir kritis siswa yang mengikuti pembelajaran matematika dengan model Problem Based Learning berbantuan masalah open-ended lebih baik daripada siswa yang mengikuti pembelajaran matematika dengan pendekatan konvensional; 2) tidak terdapat interaksi antara pendekatan pembelajaran Problem Based Learning dengan sikap matematis siswa terhadap kemampuan berpikir kritis matematika siswa. Artinya baik siswa yang memiliki sikap matematis tinggi maupun yang memiliki sikap matematis rendah apabila diajarkan dengan pendekatan pembelajaran Problem Based Learning berbantuan masalah open-ended selalu lebih baik dibanding siswa yang dibelajarkan dengan pendekatan konvensional.